HUBUNGAN TINGKAT PENGETAHUAN DAN TINDAKAN MASYARAKAT TERHADAP STANDAR RUMAH SEHAT DI DESA CUMBOK NIWA KECAMATAN SAKTI KABUPATEN PIDIE TAHUN 2022 - Razi, T. Khairol; Syahputra, Fadli; Amelia , Kiki Rezeki; Fitria , Rizka (Sagita Academia Journal, 2024)
A healthy home is one means of achieving optimum health. Coverage of healthy housing in Indonesia is still low, namely only 47.9% compared to the national target of 80%. One of the main components of obtaining a healthy home is determined by the availability of housing sanitation facilities. Aceh Province has 60% of villages that have implemented Community Based Total Sanitation (STBM) out of a total of 6,514 villages with the percentage of STBM villages still at 1%. Meanwhile, STBM data for Pidie Regency which has implemented STBM is 78% of the total 731 villages with STBM villages still 0%. This research aims to find out and get an overview of community knowledge and actions regarding healthy house standards in Cumbok Niwa Village, Sakti District, Pidie Regency. This research is analytical in nature on a population of 209 families in Cumbok Niwa Village, Sakti District, Pidie Regency. Sampling was carried out randomly in stratified manner on 68 families during January 2022. The research results showed that public knowledge of healthy home standards reached 54.4%. However, the requirements for healthy homes, sanitation and the impact of unhealthy homes are still below 50%. Community actions towards healthy home standards account for 47% and 36.7% for cleaning floors and removing rubbish, respectively. The conclusion obtained is that there is a connection between knowledge and the actions taken. This can be seen from the number of respondents who apply healthy home standards, who are highly educated respondents compared to respondents who have low education. It is recommended that the community maintain and improve the quality of healthy home standards and increase socialization or education to the public about healthy home standards